Research on the Impact of Restorative Justice Implementation on the Social Reintegration of Offenders and the Reduction of Recidivism Rates - Tianzhao Lin; Hong Chen; Jingjing Wu (Law and Economy, 2023)
Restorative justice has emerged as a powerful framework within the criminal justice system, offering innovative solutions to reduce recidivism and promote the social reintegration of individuals with criminal backgrounds. This paper explores the impact of restorative justice on these crucial aspects of the criminal justice process. It delves into the principles, practices, and theoretical underpinnings of restorative justice. Real-world cases and empirical evidence are presented to illustrate its effectiveness, while also acknowledging the challenges and limitations. The implications of this research highlight the need for wider integration of restorative justice programs, the development of skilled facilitators, and the importance of community involvement. As a holistic approach, restorative justice provides a promising path toward safer and more inclusive communities.